Gestational diabetes mellitus: management during and after pregnancy - a systematic literature review - Claudia Banowati Subarto; Mohammad Hakimi; Yuli Isnaeni (Journal of Health Technology Assessment in Midwifery, 2020)
Introduction: Gestational Diabetes Mellitus (GDM) is one of the most common complications of pregnancy. Women with gestational diabetes have a higher risk of serious health outcomes for mother and baby such as preeclampsia, premature birth and the long term development of type 2 diabetes. This study was conducted to present a review of available research in several countries about GDM management during and after pregnancy. Method: Several databases including PubMed, ScienceDirect and EBSco were searched for relevant articles published between January 2009 and January 2019. Result: Of the 1186 initial articles identified, this study analyzed 7 relevant articles that met the inclusion criteria. This study showed that management for GDM includes medical nutrition therapy, exercise, monitoring of blood glucose, and insulin therapy if blood glucose is not achieved with that treatment. Exclusive breast feeding for at least three months has been shown reducing the risk of childhood obesity of children, particularly in those born to obese and mothers with GDM Conclusion: There is a need to increase awareness of long-term consequences on gestational diabetes, both in patients and in healthcare professionals. Counseling is needed for dietary intervention and physical activity for all postpartum women with a history of GDM to stay healthy or to improve future health